2016
DOI: 10.1190/tle35110986.1
|View full text |Cite
|
Sign up to set email alerts
|

Near-surface geophysical mapping of an Upper Cretaceous submarine volcanic vent in Austin, Texas, USA

Abstract: Geophysical surveys were conducted at the Williamson Creek site south of Austin, Texas, to determine the structural relation of the Upper Cretaceous volcanic rocks (lava and tuff) with the associated Austin Chalk limestone. At this site, resistivity and magnetic methods were performed over the exposed volcanic and limestone rocks. Geophysical results indicate an excellent correlation between high-magnetic and low-resistivity anomalies. The pseudo-3D resistivity data show a steeply dipping funnel-shaped vent fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…In this study, RMS values of six inverted resistivity sections range between 3 and 8, and the seventh profile has a RMS value of 11. These are acceptable results, being of the same magnitude of the values that characterize inversion of data collected in volcanic environments [Bruno et al 2007;Loke 2000;Xia et al 2010;Di Giuseppe et al 2017;Saribudak and Caran 2015;Saribudak 2016].…”
Section: Resistivity Methodssupporting
confidence: 58%
See 4 more Smart Citations
“…In this study, RMS values of six inverted resistivity sections range between 3 and 8, and the seventh profile has a RMS value of 11. These are acceptable results, being of the same magnitude of the values that characterize inversion of data collected in volcanic environments [Bruno et al 2007;Loke 2000;Xia et al 2010;Di Giuseppe et al 2017;Saribudak and Caran 2015;Saribudak 2016].…”
Section: Resistivity Methodssupporting
confidence: 58%
“…More geophysical results (2D and 3D resistivity and magnetics) over the known outcrops of tuff and lava at the Williamson Creek site revealed a volcanic vent [Saribudak 2016]. Results of these geophysical studies [Saribudak and Caran 2015;Saribudak 2016], for the first time, revealed the presence of volcanic features that included vents, dikes and craters. This study is the extension of those previous studies, with particular emphasis on the structures of tuff mounds.…”
Section: Previous Geophysical Workmentioning
confidence: 92%
See 3 more Smart Citations